Three-dimensional computation of flow and sound for human hemilarynx. (1st August 2016) - Jo, Yongwoo; Ra, Hawoon; Moon, Young J.; Döllinger, Michael
Highlights: The power exchange between the airstreams and the human hemilarynx is 0.05 ∼ 0.175 Watts. The energy exchange for one period of glottis motion ranges from +27 to −5 µJ . The open quotient Oq around 0.5 exhibits good viscoelastic characteristics of the hemilarnyx. The open quotient Oq exceeding 0.67 actually represents anti-viscoelastic characteristics. The mucosal motions of the vocal fold is responsible for regulating the produced sound. Abstract: The flow and sound of a human hemilarynx, of which the three-dimensional surface motion (e.g. mucosal waves) is measured using the high-speed imaging techniques, are computed for R e l = 192 − 752 and M = 7.62 × 10 − 4 − 2.97 × 10 − 3 by solving the filtered incompressible Navier-Stokes equations (INS), coupled with the linearized perturbed compressible equations (LPCE). The predicted acoustic characteristics accord reasonably well to the experimental data for all Reynolds numbers, and it is found that the power exchange between the air-streams and the hemilarynx ranges from 0.05 to 0.175 Watts and the amount of energy exchange for one period of glottis motion is +27 to –5 µJ . The computational results indicate that the open quotient Qo, an indicator of phonation efficiency, is well related to the energy exchange between flow and hemilarnyx and that the three-dimensional mucosal motions of the vocal fold is responsible for regulating the produced sound over a wide range of frequencies.